Bioeconomic innovations breeding more sustainable innovations: A value chain perspective from Argentina - Jochen Dürr; Marcelo Sili; Pablo Mac Clay; Jorge Sellare (Business Strategy and the Environment, 2024)
Abstract Innovations are crucial for the transition to a sustainable bioeconomy. They are embedded in and linked to complex value chains, but these interrelationships have not received much attention in the empirical literature yet. Using current typologies of four bioeconomic innovation types and six value chain models, this case study analyzes detailed data from 11 companies in Argentina to identify the drivers of sustainable innovations, their linkage to different value chain characteristics, and the main innovation types. The results show that certain factors such as supply and demand, interindustry cooperation and R&D, diversification strategies, personal values and the search for sustainable solutions particularly shape certain types of innovation. The structure and governance of the value chains influence the type of sustainable innovation. Innovations take place at different levels, and in succession, they complement each other and can thus make the bioeconomy more sustainable. Therefore, appropriate policies to promote the bioeconomy in Argentina and beyond should consider the type of value chains and specific innovation systems involved.
Keywords: 330; biofuels; biomass; biotechnologies; food industry; governance; incremental innovations